At a Glance Information System in LMS for Education Language - Arnes Yuli Vandika; Eka Imama Novita Sari; Ade Kurniawan; Dina Ika Wahyuningsih (International Conference on Education and Language (ICEL), 2014)
Education can not be separated from the use of technology, especially educational language is sometimes very dependent on the technology itself. It is the one who pushed for the creation of creativity in technology transfer. A frequent problem in learning is often caused by the lack of media to assist students in learning and teaching activities. For that created various models of technology systems. and one of them is the LMS or Learning Management System. LMS or Learning Management System is one example for the application of advanced technology-based learning. Where the use of this technology is a very important role to provide information system to the users of this case is the students.